1991
DOI: 10.1055/s-2008-1071430
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography as an Adjunct in Etiological Analysis of Hemiplegic Cerebral Palsy; II: Children Born at Term

Abstract: CT brain scans were used to evaluate the most likely etiology of hemiplegic cerebral palsy in a group of children born at term. The population based study group comprised 83 children. The CT findings were classified to reflect the phase of brain maturation during which the injury causing hemiplegia most likely had occurred. The most common finding (37%) was periventricular atrophy considered to represent periventricular leukomalacia (PVL). PVL is a form of hypoxic-ischemic damage typical of the immature brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…Cerebral palsy can be caused by cerebral ischemia, intracranial hemorrhage, or metabolic effects on the brain of preterm and full-term infants [11][12][13]. These events often produce damage to the pyramidal tract, a major output pathway from the motor cortex to the brainstem and cranial nerve motoneurons, as well as to ascending sensory pathways and commissural and association fibers.…”
Section: Lesion Studiesmentioning
confidence: 99%
“…Cerebral palsy can be caused by cerebral ischemia, intracranial hemorrhage, or metabolic effects on the brain of preterm and full-term infants [11][12][13]. These events often produce damage to the pyramidal tract, a major output pathway from the motor cortex to the brainstem and cranial nerve motoneurons, as well as to ascending sensory pathways and commissural and association fibers.…”
Section: Lesion Studiesmentioning
confidence: 99%
“…This may vary as one class III study reported that 22.5% of 120 patients had potentially treatable lesions identified (hydrocephalus, porencephaly, arteriovenous malformation, subdural hematomas and hygromas, and a vermian tumor). 10 The majority of other studies reported either no patients with potentially treatable lesions 6,13,14 or lower incidences of 5%, 9 14%, 11 and 17%. 8 On occasion, CT (as well as MRI) may detect abnormalities that suggest a potentially treatable inborn error of metabolism.…”
Section: Description Of Processmentioning
confidence: 99%
“…Patients with hemiplegic CP frequently have suffered a prenatal or perinatal cerebral infarction. Data from three CT studies listed in table 3a (n ϭ 196) found cerebrovascular occlusion, usually in the middle cerebral artery distribution, in 13%, 6 32%, 11 and 37% 14 of individuals. There are insufficient data concerning the incidence of cerebral infarction or other causes of cerebrovascular compromise in children with other forms of CP.…”
Section: Coagulopathies Should Coagulation Studies Be Performed In Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient periventricular echo densities or periventricular leukomalacia are predictive of impaired neurodevelopmental outcome [1,3,4,[24][25][26] as well as ventricular dilatation and cerebral atrophy [19]. Computed tomography provided more accurate informations about brain damage in children born term and preterm and was considered as a major adjunct to assessment of the injury responsible for cerebral palsy [21,27] as well as an interesting tool for prediction of the later neurodevelopmental outcome [28]. However, MRI has been reported to be more sensitive in determining brain damage than computed tomography and ultrasound in both term and preterm infants [6,7] and especially in depicting the pathological signal intensity in thalami and basal ganglia [23].…”
Section: Discussionmentioning
confidence: 99%